Predictive value of a multi-biomarker disease activity score for clinical remission and radiographic progression in patients with early rheumatoid arthritis: a post-hoc study of the OPERA trial. (2nd January 2019) - Brahe, CH; Østergaard, M; Johansen, JS; Defranoux, N; Wang, X; Bolce, R; Sasso, EH; Ørnbjerg, LM; Hørslev-Petersen, K; Stengaard-Pedersen, K; Junker, P; Ellingsen, T; et al.
Abstract : Objectives : Measurement of serum biomarkers at disease onset may improve prediction of disease course in patients with early rheumatoid arthritis (RA). We evaluated the multi-biomarker disease activity (MBDA) score and early changes in MBDA score for prediction of 28-joint Disease Activity Score based on C-reactive protein (DAS28-CRP) remission and radiographic progression in the double-blinded OPERA trial. Method : Treatment-naïve RA patients (N = 180) with moderate or high DAS28 were randomized to methotrexate (MTX) + adalimumab (n = 89) or MTX + placebo (n = 91) in combination with glucocorticoid injection into swollen joints. X-rays of hands and feet were evaluated at months 0 and 12 (n = 164) by the total Sharp van der Heijde score (TSS). The smallest detectable change (1.8 TSS units) defined radiographic progression (∆TSS ≥ 2). Clinical remission (DAS28-CRP < 2.6) was assessed at baseline and 6 months. MBDA score was determined at 0 and 3 months and tested in a multivariable logistic regression model for predicting DAS28 remission at 6 months and radiographic progression at 1 year. Results : Baseline MBDA score was independently associated with radiographic progression at 1 year [odds ratio (OR) = 1.03/unit, 95% confidence interval (CI) = 1.01–1.06], and changes in MBDA score from baseline to 3 months with clinical remission at 6 months [OR = 0.98/unit, 95% CI 0.96–1.00). In anti-cyclic citrullinated peptide antibody (anti-CCP)-positive patients, 35 of 89 with high MBDA score (> 44) showed radiographic progression (PPV = 39%), compared with 0 of 15 patients (NPV = 100%) with low/moderate MBDA score (≤ 44) (p = 0.003). Conclusion : Early changes in MBDA score were associated with clinical remission based on DAS28-CRP at 6 months. In anti-CCP-positive patients, a non-high baseline MBDA score (≤ 44) had a clinical value by predicting very low risk of radiographic progression at 12 months.